Sarbanes-Oxley : IT compliance using COBIT and open source tools - Lahti, Christian (Syngress Pub., 2005)
Illustrates the Open Source cost savings opportunities available to companies seeking Sarbanes-Oxley compliance. This book also provides examples of the Open Source infrastructure components that can and should be made compliant. It also documents which Open Source tools you should consider using in the journey towards compliance.